The Critical Role of Carbon in the Chemical Delithiation Kinetics of LiFePO4. Issue 7 (19th March 2020) - Galceran, Montserrat; Guerfi, Abdelbast; Armand, Michel; Zaghib, Karim; Casas-Cabanas, Montse
Abstract : The chemical delithiation of LiFePO4 has been carefully studied using two different types of LiFePO4 : (1) carbon coated LiFePO4 and (2) non-carbon coated LiFePO4 . We have observed that only carbon coated LiFePO4 can be successfully delithiated at room temperature using Na2 S2 O8 as oxidizing agent. In order to unravel the role of carbon in the chemical delithiation process of non-carbon coated LiFePO4 we have performed a systematic study using different carbon sources as well as different amount of extraneous carbon in the solution. The results obtained demonstrate that the addition of carbon is fundamental for the effective removal of lithium at room temperature, and only a very small amount of carbon of any nature is enough to achieve the successful chemical delithiation of non-carbon coated LiFePO4 .